Prevalence and factors associated with probable obstructive sleep apnea among patients with hypertension in two primary care clinics in Miri, Sarawak, Malaysia - Ching, Siew Mooi; Singh, Rajvinder; Azmi, Fatimah Shahidah; Chong, Khian Lu; Ong, Cynthia Ruey Shyuan; Ayob, Nur Afiqah; Patil, Mansi; Lee, Kai Wei; Ramachandran, Vasudevan; Arora, Viresh (Springer Science and Business Media Deutschland GmbH, 2023)
Purpose: Obstructive sleep apnea (OSA) has been increasingly recognized as an important factor contributing to medical morbidity and mortality. It was reported that more than half of the population with hypertension had OSA. Limited studies have been done on assessing OSA in hypertensive patients. This study aimed to determine the prevalence, socio-demographic characteristics, and factors associated with probable OSA in hypertensive patients in primary care clinics in Sarawak. Methods: A cross-sectional study was carried out using a systematic random sampling method in hypertensive patients who attended two government primary care clinics in Sarawak. The STOP-Bang questionnaire was used to screen for OSA, and social-demographic data was captured with a questionnaire. Multiple logistic regressions were used to examine the determinants of the OSA. Results: A total of 410 patients were enrolled in this study. The mean age of study population patients was 56.4 years, with more than half being female. The mean blood pressure was 136/82. The prevalence of probable OSA among patients with hypertension was 54.4. According to multiple logistic regression analyses, smoking (odds ratio OR 14.37, 95% confidence interval CI 3.335–61.947), retirees (OR 3.20, 95% CI 1.675–6.113), and being Chinese (OR 2.21, 95% CI 1.262–3.863) had a significant positive association with probable OSA. Conclusions: Because of the high prevalence of probable OSA among patients with hypertension, primary care physicians should be more vigilant in identifying hypertensive patients with OSA risk. Early detection and intervention would reduce disease complications and healthcare costs.